PENGARUH INFLASI, NILAI TUKAR, CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM (Studi Kasus Pada PT. Eratex Djaja, Tbk Periode 2009-2011) - Muhammad Gusvarizon (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
This study entitled "Influence Analysis of Inflation, Exchange Rate, Current Ratio (CR) and Debt to Equity Ratio (DER) on Stock Price (Case Study At PT Eratex Djaja, Tbk Listed on Indonesia Stock Exchange Period 2009 - 2011). In this research use survey research method with correlational and predictive approach. By taking sample that is PT. Eratex Djaja, Tbk Listed on Indonesia Stock Exchange Period of quarter 2009 - 2011. To solve the problem by analyzing and testing the relationship and influence between independent variable to dependent variable used by causalistic model through regression analysis with the help of SPSS 14.0. The result of this research is simultaneously Inflation, Exchange Rate, Current Ratio (CR) and Debt to Equity Ratio (DER) have positive and significant influence to Stock Price. Partially that: Inflation gives effect to Stock Price with influence of 44% (strong enough), Exchange Rate gives influence to Share Price with influence of 56% (strong enough), Current Ratio (CR) gives effect to Stock Price with influence equal to 76% (strong) and Debt to Equity Ratio (DER) give effect to Share Price with influence equal to 71% (strong).